(3GdTYGYGJ GdTeSjIs - (3jYbhH Hf ESMGb Hf GdUHGM GdcfOj, CHh jhSa,J (B260 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3CWGd Gddg HbGA GdeDefjf hCOGe YRI hJCjjOgCfg djS jUZQ GdNWQ Yde eNGQL GdTYGYGJ GdTeSjI hEfYcGSGJgG s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B244s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B209 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B59 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs